Nephrocalcinosis and proximal tubulopathy in Sjögren's Syndrome - Baenas, Diego Federico (2018)
Primary Sjögren´s syndrome is a systemic and chronic autoimmune disease. Renal involvement may occur in up to 30% of patients. The incidence of tubulopathies ranges from 2.6 to 33%. They are manifested by defects in the urine concentration and hydroelectrolyte alterations, mainly distal tubular acidosis and exceptionally proximal tubular acidosis. These disorders can be associated with nephrocalcinosis and renal lithiasis. We report the case of a patient with primary Sjögren who presented proximal renal tubular acidosis associated with recurrent renal colic due to renal lithiasis and nephrocalcinosis. We highlight the importance of diagnosing renal tubular acidosis in patients with Sjögren´s syndrome that present alterations in urinary sediment and electrolyte disorders to avoid nephrocalcinosis and nephrolithiasis. Acidosis correction treatment aims to prevent the progression of the disorder and preserve renal function.